2013
DOI: 10.1097/aln.0b013e31827dde8d
|View full text |Cite
|
Sign up to set email alerts
|

Does Low-dose Droperidol Increase the Risk of Polymorphic Ventricular Tachycardia or Death in the Surgical Patient?

Abstract: Background:The Food and Drug Administration issued a black box warning regarding the use of droperidol and the potential for torsade de pointes. Methods: The primary objective of this retrospective study was to determine if low-dose (0.625 mg) droperidol administration was associated with episodes of torsade de pointes in the general surgical population during the 3-yr period following the reinstitution of droperidol to our institutional formulary. Results:The authors identified 20,122 surgical patients who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 13 publications
1
15
0
1
Order By: Relevance
“…Its ability to prolong the QT interval has been attributed to its action to block the rapid component of the delayed rectifier potassium current within myocytes (Drolet et al, 1999). However, recent studies have shown that the low doses of droperidol used for PONV prophylaxis do not increase the risk for arrhythmia formation or cardiac death (Nuttall et al, 2007; Nuttall et al, 2013). This recent data suggests that the low doses used to potentially prevent PONV are likely safe.…”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…Its ability to prolong the QT interval has been attributed to its action to block the rapid component of the delayed rectifier potassium current within myocytes (Drolet et al, 1999). However, recent studies have shown that the low doses of droperidol used for PONV prophylaxis do not increase the risk for arrhythmia formation or cardiac death (Nuttall et al, 2007; Nuttall et al, 2013). This recent data suggests that the low doses used to potentially prevent PONV are likely safe.…”
Section: Pharmacological Therapiesmentioning
confidence: 99%
“…That study included 20 122 persons receiving a total of 35 536 doses of 0.625 mg of droperidol intravenously. Eight hundred and fifty‐eight of those individuals had ECG charts that could be analyzed and no one developed polymorphic ventricular tachycardia or death as a direct result of droperidol administration . On the other hand, TdP has clearly been reported associated with droperidol in cases published in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a black box warning on droperidol, there are many studies demonstrating its safety. [7][8][9][10][11][12] Adverse effects to be aware of are extrapyramidal syndrome and QT-interval prolongation. The QT-interval effects are unlikely to be clinically significant and rarely precipitate torsades de pointes.…”
Section: "We Have the Drugs They Have The Receptors"mentioning
confidence: 99%
“…The QT-interval effects are unlikely to be clinically significant and rarely precipitate torsades de pointes. 7,10 Benzodiazepines have relatively quick onset, are safe, and can be rapidly titrated to effect. They can be used alone or in combination with antipsychotics.…”
Section: "We Have the Drugs They Have The Receptors"mentioning
confidence: 99%